Identifying the relationships between personality and behavior in adolescents - Calin, Mariana Floricica; Sandu, Mihaela Luminita; Zburlea, Ana (Technium Social Sciences Journal, 2021)
Any individual at least once during his development goes through a state of anxiety or depression due to the social context in which the individual is interdependent with his personality at a certain stage in ontogenesis. Adolescence being a stage in human development characterized by countless turbulences, a fragile and unstable personality in constant change, is a good place for the appearance of anxious or depressive behaviors. Personality traits are the predictors of anxiety and depression, a fact addressed in many researches in the literature. This paper has as a starting point the desire to capture the extent to which personality factors in the Big-Five Model make a prediction for anxiety and depression during adolescence. Emotional stability, extraversion and conscientiousness are the personality factors from which we started to measure the level of anxiety and depression of adolescents. The present paper starts from these predictors of anxiety and depression during adolescence and aims to identify the implications of these conditions on adolescents and also aims to investigate whether the high school profile of the adolescent has some influence on the level of anxiety. Regarding the level of anxiety depending on the profile of the high school graduated by adolescents, this research addresses this topic from the perspective of a relatively small sample of participants, which may be a limitation of the research.